Chemoenzymatic conversion of Sorghum durra stalk into furoic acid by a sequential microwave-assisted solid acid conversion and immobilized whole-cells biocatalysis. (September 2020) - Ma, Zheng; Liao, Zhijun; Ma, Cuiluan; He, Yu-Cai; Gong, Chunjie; Yu, Xiaoping
Graphical abstract: Highlights: Microwave-assisted Sn-argil converted biomass into furfural in biphasic media. High distribution coefficient ( Kd ) in organic solvent could enhance furfural yields. Furfural was oxidized to furoic acid by immobilized Brevibacterium lutescens cells. Reuse of Sn-argil and immobilized cells was conducted for synthesis of furoic acid. Chemoenzymatic strategy was developed for converting SDS to furoic acid. Abstract: In this study, chemoenzymatic conversion of Sorghum durra stalk (SDS) into furoic acid was developed by a sequential microwave-assisted solid acid conversion and immobilized whole-cells biocatalysis method. Dry dewaxed SDS (75 g/L) was catalyzed into furfural at 57.8% yield with heterogeneous Sn-argil (2.0 wt% dosage) in n-ethyl butyrate-H2 O (1:1, v:v) biphasic system using a microwave (600 W) for 10 min at 180 °C. In this biphasic media (pH 6.5), SDS-derived furfural (125.0 mM) was biologically oxidized to furoic acid by immobilized Brevibacterium lutescens cells harboring furfural-oxidizing activity at 30 °C, and furfural was wholly transformed to furoic acid within 24 h. Finally, the recovery and reuse of the Sn-argil catalyst and immobilized biocatalysts were conducted for synthesizing furoic acid from SDS in the biphasic system. This chemoenzymatic route can be attractive for furoic acid production.